2014
DOI: 10.1136/bjsports-2014-093494.129
|View full text |Cite
|
Sign up to set email alerts
|

Small Multifidus Muscle Size Predicts Football Injuries

Abstract: Background: In Australian football, lower limb injuries have had the highest incidence and prevalence rates. Previous studies have shown that football players with relatively more severe preseason and playing season hip, groin, and thigh injuries had a significantly smaller multifidus muscle compared with players with no lower limb injuries. Rehabilitation of the multifidus muscle, with restoration of its size and function, has been associated with decreased recurrence rates of episodic low back pain and decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 32 publications
2
34
1
Order By: Relevance
“…However, in the playing season, smaller size of either the multifidus muscle or the QL muscle was predictive of injury (Hides & Stanton, ). The results for the multifidus muscle were confirmed in a second study with a larger cohort consisting of 259 professional football players, which showed that decreased size of the multifidus muscle at the L5 vertebral level consistently predicted injury in both the pre‐season and playing season periods (Hides et al., ).…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…However, in the playing season, smaller size of either the multifidus muscle or the QL muscle was predictive of injury (Hides & Stanton, ). The results for the multifidus muscle were confirmed in a second study with a larger cohort consisting of 259 professional football players, which showed that decreased size of the multifidus muscle at the L5 vertebral level consistently predicted injury in both the pre‐season and playing season periods (Hides et al., ).…”
mentioning
confidence: 76%
“…Independent samples of players were drawn from the player lists of six AFL clubs (261 players) that agreed to participate in a study of the relationship between muscle morphology and injury. Results for the multifidus muscles for the whole dataset have been published previously (Hides et al., ). Within the time constraints to access players, imaging of the QL muscle was obtained from a subset of 62 players at the start of the pre‐season, and 102 players at the start of the playing season.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have shown that increased muscle strength and size reduces the risk of injuries. [10][11][12][13] Ultrasound imaging is a relatively inexpensive, portable, non-ionizing, non-invasive and real-time diagnostic modality. Ultrasound imaging is therefore proposed as a means to complement the usual medical assessment approaches by objectively assessing each muscle in the cervical region, and describing size norms for front row players which could be correlated to cervical protective support towards injury prevention in future studies.…”
Section: Introductionmentioning
confidence: 99%